The specifics of the appointment of forensic examinations in the investigation of corruption-related crimes committed in cyberspace - Тіщенко, Валерій Володимирович; Тіщенко, В. В.; Тищенко, Валерий Владимирович; Tishchenko, Valerii V.; Бєлік, Лариса Степанівна; Бєлік, Л. С.; Белик, Лариса Степановна; Bielik, Larysa S.; Самойленко, Олена Анатоліївна; Самойленко, О. А.; Самойленко, Елена Анатольевна; Samoilenko, Olena A. (Editorial Primmate S. A. S., 2019)
Relevance. The study is relevance due to the problem of cybercrime, including corruptionrelated crimes, which were caused by the rapid worldwide development of computer technology, as well as the widespread use of cyberspace networks and the digitization of information-sharing processes in society. The object of the study is the public relations that arise in the process of judicial expertise in the investigation of corruption-related crimes committed in cyberspace. Several research methods have been used in the writing of this research article. The dialectical method was the first and foremost method in the study of judicial expertise. The method of analysis, the synthesis method, and comparison method were used during the research process. Research results. The authors of this scientific article came to the conclusion that the specific nature of the use of forensic investigations in the investigation of corruption offenses committed in cyberspace is one of the main forms of use of specialized knowledge in criminal proceedings and the result of which is the conclusion of expert opinion, which is the source of evidence in criminal proceedings. In addition, it was noted that all the issues that are solved by the examination of telecommunication systems (equipment) and tools have a diagnostic nature, and a list of typical issues should be fixed in the appropriate instructions.

Актуальність. Актуальність статті зумовлена ростом числа злочинів вчинених у кіберпросторі, вчиненні яких стало можливим через стрімкий загальносвітовий розвиток комп’ютерних технологій, поширення використання мереж кіберпростору та діджиталізація процесів обміну інформації у суспільстві, та злочинів корупційної спрямованості. Об’єктом дослідження є суспільні відносини, що виникають у процесі проведення судових експертиз при розслідуванні злочинів корупційної спрямованості, вчинених у кіберпросторі. У написанні даної наукової статті було використано кілька методів дослідження. Діалектичний метод був першим і головним методом вивчення процесу призначення судової експертизи. Окрім цього, у процесі дослідження використовували метод аналізу, метод синтезу, метод порівняння тощо. Результати дослідження. Автори даної наукової статті прийшли до висновків, що специфіка призначення судових експертиз при розслідуванні злочинів корупційної спрямованості, вчинених у кіберпросторі представляється однією з головних форм використання спеціальних знань в кримінальному процесі і результатом якого є складання експертного висновку, що є джерелом доказу у кримінальному провадженні. Окрім цього, було зазначено, що всі питання, які вирішує експертиза телекомунікаційних систем (обладнання) та засобів, мають діагностичний характер, а перелік типових питань доцільно закріпити у відповідній інструкції.
Tishchenko V. The specifics of the appointment of forensic examinations in the investigation of corruption-related crimes committed in cyberspace / V. Tishchenko, L. Bielik, O. Samoilenko // Amazonia Investiga. – Vol. 8. - Issue 24. – Editorial Primmate S. A. S., 2019. – P. 280-287.
Keywords: judicial expertise; crime investigation; corruption; cyberspace; corruptionrelated crimes; crime; судова експертиза; розслідування злочинів; корупція; кіберпростір; корупційні злочини; злочини; Research Subject Categories::LAW/JURISPRUDENCE